2023
DOI: 10.1186/s12891-023-06877-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying strategies that support equitable person-centred osteoarthritis care for diverse women: content analysis of guidelines

Chidinma Abuwa,
Angelina Abbaticchio,
Madeline Theodorlis
et al.

Abstract: Introduction Women are disproportionately impacted by osteoarthritis (OA) but less likely than men to access early diagnosis and management, or experience OA care tailored through person-centred approaches to their needs and preferences, particularly racialized women. One way to support clinicians in optimizing OA care is through clinical guidelines. We aimed to examine the content of OA guidelines for guidance on providing equitable, person-centred care to disadvantaged groups including women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…20 Doing all that is possible to improve the stressful experiences of cumulative social deprivation such as deficits in educational opportunities, health care access, racial discrimination, race-based implicit biases and others, do appear to contribute to a high degree in terms of unsatisfactory orthopedic-related outcomes observed for some minority groups and others, especially the socio economically disadvantaged groups and its members and warrant dedicated attention. 40,[67][68][69] In this regard, three points offered by observations of Abuwa et al, 70…”
Section: Discussionmentioning
confidence: 93%
“…20 Doing all that is possible to improve the stressful experiences of cumulative social deprivation such as deficits in educational opportunities, health care access, racial discrimination, race-based implicit biases and others, do appear to contribute to a high degree in terms of unsatisfactory orthopedic-related outcomes observed for some minority groups and others, especially the socio economically disadvantaged groups and its members and warrant dedicated attention. 40,[67][68][69] In this regard, three points offered by observations of Abuwa et al, 70…”
Section: Discussionmentioning
confidence: 93%
“…This study found that many guidelines lacked person-centred care content, and even when mentioned, details were brief, providing little assistance to clinicians who have advocated for greater guidance ( Bourque & Foley, 2020 ; Koch et al, 2010 ; Mansfield et al, 2019 ) given lack of training in person-centred care ( Anderson & Gagliardi, 2021a ; 2021b ). This raises the question of why included dementia guidelines, and guidelines on other topics did not address person-centred care for women ( Abuwa et al, 2023 ; Gagliardi et al, 2019 ). Notably, few guidelines included in this study involved women living with dementia or caregivers in their development.…”
Section: Discussionmentioning
confidence: 99%